The Influence of Client Design Demands on Sleep Quality of Architectural Consultant Office Employees(Case Study: at Pt Narendra Karya) - Alfina Hafidhoh; Ema Mayasari (Galen: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Client design demands are one of the most common work demands faced by employees in architectural consulting firms. Design diversity, frequent changes in requirements, stringent quality control, and deadline pressures can increase mental stress and potentially impact employee sleep quality. This study aimed to explore the relationship between client design demands and sleep quality among employees at the PT Narendra Karya Architectural Consulting Firm. The methodology employed was a quantitative, observational, and analytical design with a cross-sectional approach. The sample size for this study was 33 employees, selected using a total sampling method. Information regarding client design demands was obtained through a questionnaire developed based on the Job Demands-Resources (JD-R) framework, while the Pittsburgh Sleep Quality Index (PSQI) was used to measure sleep quality. Data were analyzed using univariate analysis, bivariate analysis using the Spearman Rank test, and multivariate analysis using logistic regression. The findings indicated a significant relationship between client design demands and employee sleep quality (p = 0.021). The Exp(B) value of 1.621 indicates that increasing client design demands increases the likelihood of sleep quality problems. The results of this study indicate that the greater the design demands faced by employees, the higher the risk of their sleep quality declining. Therefore, companies should implement more planned workload management by setting achievable work targets, systematically organizing design revision processes, and efficiently managing deadlines to maintain employee health and sleep quality.